Experimental Study on Effect of Partial Replacement of Coarse Aggregates in Concrete by Waste Tyre Rubber Aggregates in Rigid Pavements (International Journal of Innovative Research in Engineering & Management, 2022)
Our study intends to explore the flexural  and split tensile strength, light weight, higher impact and  toughness resistance which means prolonged and better  resistance to formation of cracks, upgraded ductility, etc  most effective use of the waste tyre rubber as a constituent  of concrete mix replacing the coarse aggregate partially. In  this research work, emphasis is given on the pre-treating of  the rubber particles and then using them as the partial  replacement of the conventional rock aggregates. To get  the best results, the rubber aggregates used are surface  treated by sodium hydroxide and cement paste before  using them in the concrete.M20 grade concrete is used.  Using untreated rubber aggregates, the compressive  strength of the resultant concrete reduced rapidly, but when  treated rubber aggregates were introduced, it resulted in the  regaining of more than 90% of the 28 day compressive  strength of normal concrete which can be considered quite  satisfactory considering the easy and cheap availability of  the used tyres and the negative impacts it can have on the  environment if left unused. This much compressive  strength is enough for treated-rubberized concrete for its  use in different areas where compressive strength is not  much important like in floors and concrete road  pavements. Flexural and split tensile strength is found to  be higher than that of the normal concrete but only when  treatment is given to the rubber aggregates before using  them. Workability is decreased. Flexibility gets increased  and due to the lower unit weight of the rubber particles, it  is also lighter than the normal concrete.
Keywords: M2O; Toughness Resistance; concrete mix; Split Tensile Strength; Light Weight Concrete